The Relationship between Student Learning Motivation and Classroom Management with Student Learning Outcomes at the YLPT Academy of Optician Refraction Padang - Rina Novalinda; Dolly Iman Suryanta (Edumaspul: Jurnal Pendidikan, 2023)
The problem in this study is that student learning outcomes are low and learning motivation is lacking. The type of research used is causative research. The population in this study were all fourth semester students at the YLPT Padang Optic Refraction Academy, totaling 45 people. The sample uses total sampling technique so that the total sample is 45 people. The instrument used is a questionnaire (questionnaire). Data were analyzed using data description techniques, requirements testing and hypothesis testing. Based on the findings, several conclusions can be drawn 1) Learning Motivation is related to student learning outcomes. This result shows that the t count > t table or sig value < 0.05. 2) Management of class management is related to student learning outcomes of t count> table or si g< 0.05 values. 3) Learning motivation and classroom management are jointly related to student learning outcomes with F count > F table